Traditional Ukrainian Folk Beliefs about Death and the Afterlife - Kukharenko, Svitlana (FOLKLORICA - Journal of the Slavic, East European, and Eurasian Folklore Association, 2012)
In contemporary Ukraine, there exist various memorials that mark places of tragic death. These can be found on any road in large numbers. They can also be found elsewhere, including in city centers. To understand this phenomenon it is necessary to examine Ukrainian attitudes towards death. The most complete descriptions of folk beliefs about death date from the late 19th century. In Ukrainian culture death was viewed as a natural and integral part of human life and the dead could communicate with the living and vice versa. There were considered to be two types of death. “Good death” was something to strive for and, in a way, welcome and the preparation of the body and its burial followed prescribed rituals. A “bad death” was that of a suicide, a murder victim, or a person killed in an accident. Such people were not given the normal funerary rites and they were usually buried by road sides, not in the cemetery. Their souls were believed to wander the earth and could harm the living. In most cases the site of a “bad death” would be memorialized and this tradition is preserved in present day Ukraine. There are also cases of ambiguous death, such as the death of small children or women who die in childbirth. This article surveys traditional death beliefs and practices to provide information useful in understanding Ukrainian culture.